ULTRASONIC SURGERY IN OTORHINOLARYNGOLOGY: NEW FRONTIERS FOR PRECISE AND SAFE INTERVENTION (Ustozlar uchun, 2026)
In otorhinolaryngology (head and neck surgery), surgical missions in low- and middle-income countries (LMICs) are increasingly vital. Maintaining high standards of care in resource-limited settings is a challenge that requires innovative, portable, and cost-effective solutions. Recent advancements, such as tablet-based and handheld point-of-care ultrasonography (POCUS), have revolutionized perioperative care, allowing for real-time diagnostics, guided biopsies, and monitoring where CT or MRI access is restricted. Simultaneously, the integration of piezosurgery—already established in dentistry—into rhinosurgery offers a more precise alternative to traditional mechanical tools (drills and chisels), which often carry risks of hemorrhage and thermal tissue damage.